Keterlibatan Pasien dalam Aktivitas Meningkatkan Patient Safety - Armidayanti, Armidayanti; Arafat, Rosyidah; Rachmawaty, Rini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This review aims to examine patient engagement in care activities to improve patient safety. The research method uses an integrative literature review. A systematic search was carried out in the databases PubMed, ProQuest, Science Direct, Medline, Cochrane Library and Winley Online Library. The keywords used in the search are: (Patient participation OR Patient involvement OR Patient engagement) AND (Health care OR Care) AND (Patient safety). Articles must come from international databases, be published within the last 5 years and focus on patient engagement, care and patient safety with full text. Articles will be excluded if they do not focus on objectives, are more than 5 years old and if they have been reviewed. As a result of research, nine articles identified in this review that the patient's role in care can improve patient safety and the nurse's role in encouraging patients to participate in care can contribute to improving patient safety. In conclusion, patient involvement in patient safety activities can improve the safety of patients in hospitals. Keywords: Patient Safety, Patient Involvement, Care